The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1039/c3py21104e
|View full text |Cite
|
Sign up to set email alerts
|

Dual-functional materials via CCTP and selective orthogonal thiol-Michael addition/epoxide ring opening reactions

Abstract: Poly(glycidyl methacrylate) (PGMA) has been synthesised by cobalt catalysed chain transfer polymerisation (CCTP) yielding, in one step, polymers with two points for post polymerisation functionalisation; the activated terminal vinyl bond and in chain epoxide groups. Epoxide ring-opening and a combination of thiol-Michael addition and epoxide ring-opening has been used for the post-functionalisation with amines and thiols to prepare a range of functional materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…Theoretically, the reaction of polyGMA and cysteamine (CYS) is a 1:1 reaction with the primary amine of the CYS attaching to the GMA epoxide group; however, it has been reported that the CYS-GMA reaction has an efficiency of 58% [32]. Therefore, 1 g (0.007 moles) of polyGMA and 0.935 g (0.012 moles) of CYS were needed for the reaction.…”
Section: Preparing Polygma-cys-ag Polymer Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, the reaction of polyGMA and cysteamine (CYS) is a 1:1 reaction with the primary amine of the CYS attaching to the GMA epoxide group; however, it has been reported that the CYS-GMA reaction has an efficiency of 58% [32]. Therefore, 1 g (0.007 moles) of polyGMA and 0.935 g (0.012 moles) of CYS were needed for the reaction.…”
Section: Preparing Polygma-cys-ag Polymer Complexmentioning
confidence: 99%
“…The amount of DMSO and DI water were based on previous studies [24,30]. This mixture was covered with Parafilm and stirred at 600 rpm, 60 • C for 6 h. The solvents and experimental conditions were based on literature [24,32]. The contents of the beaker were centrifuged for 3 min at 112× g (times gravity) to harvest the polyGMA-CYS from the solution.…”
Section: Preparing Polygma-cys-ag Polymer Complexmentioning
confidence: 99%
“…Particularly, many studies have been attempting to develop new functionalization techniques, to allow the production of functionalized polymer materials that may interact more efficiently with specific enzymes. [ 5–15 ]…”
Section: Introductionmentioning
confidence: 99%
“…Thus, distinct polymer structures can be synthesized, new surfaces and interfaces can be produced and new materials with distinct properties can be obtained through functionalization reactions. [ 6–17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Typically, low spin cobalt(II) complexes are used as catalytic chain transfer agents, and are only required in ppm amounts relative to the concentration of monomer due to extremely high chain transfer constants when compared with other chain transfer agents, such as thiols or halocarbons. [32][33][34][35] The generally accepted mechanism for the CCTP of methacrylates proceeds via a two-step reaction, Scheme 1. 36 The process is highly adaptable, and polymers produced by CCTP have found applications within hair care, 37 as toner for printing applications, 38 and have also been used for the synthesis of low-VOC (Volatile Organic Compound) high solid coatings.…”
Section: Introductionmentioning
confidence: 99%